Integrating Islamic Values in Community Service: Strengthening Competence and Character in Vocational Education - Izuddin Syarif; Achmad Supriyanto; Syamsul Hadi; Asep Sunandar; Supriyanto Supriyanto; Fantika Febry Puspitasari; Sumarno (Nazhruna: Jurnal Pendidikan Islam, 2026)
This study investigates the effectiveness of community service-based learning in electrical installation techniques for vocational high school students in South Kalimantan. It addresses key challenges in vocational education, including the gap between hard and soft skills, limited practical facilities, insufficient character formation, and weak community participation. Using a qualitative case study with an Accidental Ethnography approach, data were gathered from 89 respondents through observation, interviews, and documentation from 2020 to 2024. The findings reveal that students’ involvement in home electrical installation repairs enhances both their technical competence and customer satisfaction, as indicated by reliability, assurance, attention, responsiveness, and tangible results. Values of social worship, intention, responsibility, and care were effectively internalized, reaching an average achievement of 92%. The program achieved a 100% completion rate and over 96% customer satisfaction. In total, 412 students contributed to 226 service points in 88 households, making community homes serve as contextual learning laboratories that also address limited school facilities. Since 2024, interschool collaboration has expanded the program’s reach and impact. The study concludes that community service-based learning transforms vocational education by producing graduates who are technically skilled, ethically grounded, and socially beneficial, reinforcing emotional, social, and spiritual intelligence.